Analisis Finansial Usahatani Lada Putih (Piper Nigrum Linn) Di Desa Ratu Sepudak Kecamatan Galing Kabupaten Sambas Provinsi Kalimantan Barat - Imelda, Yazmi, Adi Suyatno, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
Yazmi, Financial Analysis of White Pepper Farmers (Piper Nigrum Linn) Business in Desa Ratu Sepudak Kecamatan Galing Kabupaten Sambas Provinsi Kalimantan Barat under the guidance of Dr. Ir. Adi Suyatno, MP as the first supervisor and Imelda, SP., M.Sc as the second supervisor. This research aims to evaluate the financial feasibility of farming the white pepper in desa Sepudak kecamatan Galing kabupaten Sambas provinsi Kalimantan Barat. The research location is determined intentionally (purposive sampling) with the consideration that the area is one of the areas that became the center of the pepper and potential areas for development of pepper plants which all farmers who get help seed the pepper through facilitation of seeds events in order to development pepper as research object ( 71 people). The analysis of data use NPV, Net B / C, IRR, Payback Period and Sensitivity. The results showed that the farming of white pepper that has 1 hectare is Rp. 1107063450 with operational costs Rp. 351 250 744. If the interest rate of 9% per year, then the NPV is achieved is Rp. 770.812706, Net B / C ratio of 3.15, an IRR of 79.56% and a payback period for 3 years 4 months. Based on the criteria of this investment, the white pepper farms in desa Ratu Sepudak deserve financially on the run. The sensitivity analysis shows that the business remains viable for grown despite an increase in operational costs such as wages rise by 15% per year, assuming a fixed benefit, decrease in selling prices by 56.99% and seed procurement costs included in cost of investment. Analysis shows switching value if the decline in selling price by 87.3%, or Rp. 20 432 per kg and a decrease in productivity of 87.3% or 511 kg / ha at which the productivity of farmers do not benefit or loss (breakeven).Keywords : Financial Analysis, Farming White Pepper, Sensitivity Analysis.